Modern Treatment of Tongue Cancer: A Narrative Review - Siti Rusdiana Puspa Dewi; Muhammad Irsan Saleh; Krisna Murti; Nita Parisa (Indonesian Dental Association, 2026)
Introduction: Tongue cancer is cancer that develops from the tongue epithelial cell. The mortality rate was 0.7/100,000 people all over the world. Modern therapy for this cancer is based on a better understanding of the molecular and cellular mechanisms of tongue cancer. Objective: The narrative review aims to analyze the modern treatment of tongue cancer. Methods: This study was conducted using a narrative literature review methodology. Relevant articles published from 2015-2025 were identified through a systematic search of electronic databases. The initial search yielded 2,837 records. Following the removal of duplicates and the screening of titles, abstracts, and full-text articles based on the inclusion and exclusion criteria, 45 articles were deemed eligible and included in the final review. Results: Modern cancer therapies have been developed not only to provide more selective targeting of cancer cells but also to minimize or eliminate treatment-related side effects. Current therapeutic strategies can be broadly classified into four major approaches: (1) inhibition of uncontrolled cell proliferation, (2) induction of apoptosis in cancer cells, (3) prevention of tissue invasion and metastasis, and (4) inhibition of angiogenesis. Conclusion: Advances in tongue cancer treatment have been largely driven by a growing understanding of the molecular mechanisms underlying tumor development and progression. These molecular insights have facilitated the development of targeted therapeutic approaches aimed at improving treatment efficacy while reducing adverse effects. However, a limitation of this narrative review is the lack of discussion regarding the toxicological profiles of emerging therapeutic agents. Consequently, the potential adverse effects and safety considerations associated with these anticancer therapies were not comprehensively addressed.